Strategi Guru dalam Meningkatkan Perkembangan Bahasa Anak Usia 5-6 Tahun Di TK Al-Kautsar - Adzkia Aulia; Amalia Rahma; Najla’ Afifah Hulwah (Fakultas Tarbiyah IIQ Jakarta, 2022)
Language development has a very important role in the growth and development of children, it is said to support children's development because language is what supports development in other fields in the child's life. Language is an important and very important thing in human life. However, various factors can affect a person's language process, so that a person or child may experience disturbances in their language processes, such as speech delays. This study aims to determine the factors that affect speech delay in children and also the treatment given by parents and the environment in order to respond to this problem. This research uses a quantitative method with a case study approach. The resource persons in this study amounted to 3 people consisting of 3 people (1 principal and 2 teachers). Data collection techniques in this study used interviews, observations, field notes, and supporting documentation to strengthen the truth of the data taken. Based on our research on two children with language barriers at Al-Kautsar Kindergarten, we found two different factors that caused speech delay in these children. In the first child, it is caused by bilingual communication at home, then in this child the parents also cannot accept if their child is asked to have language barriers, while in the second child it is caused by a lack of parental attention because one of the parents is seriously ill. However, what we observed even though the differences in these factors could result in the same impact as a lack of focus on children, not being able to socialize well, not being able to pronounce articulation well, and other impacts that are characteristics of speech delay